Morphological Diversity and Genetic Relationships in Pulque Production Agaves in Tlaxcala, Mexico, by Means of Unsupervised Learning and Gene Sequencing Analysis - Trejo, Laura; Reyes, Miguel; Cortés-Toto, Daniela; Romano-Grande, Elvira; Muñoz-Camacho, Lizbeth L. (Frontiers in Plant Science, 2020)
Pulque is one of the oldest fermented beverages, with its origins dating back to pre-Hispanic Mexico. Recently, public consumption has increased. However, the majority of Agave plantations for pulque production have disappeared or been abandoned in recent decades. To create strategies for the conservation and production of pulque agaves, it is necessary to first determine their taxonomic identities and to better understand their genetic and morphological diversity. Despite the historical importance of pulque in Mexico, little attention has been placed on the study of Agave plants used for its production. Therefore, we analyzed the morphological diversity of vegetative characters of nine landraces of two Agave species (A. salmiana and A. mapisaga) which are widely cultivated for pulque production in Tlaxcala, Mexico. The analysis of morphological characters showed that the landraces largely clustered based on classic taxonomic relationships. One cluster of landraces associated with Agave mapisaga var. mapisaga and another with A. salmiana subsp. salmiana, but with the exception of A. salmiana subsp. salmiana “Ayoteco”, which is more closely related with A. mapisaga var. mapisaga. Additionally, we analyzed the genetic relationships between 14 landraces and wild individuals using molecular markers (trnL and ITS). The identified genetic variants or haplotypes and genetic pools mainly corresponded with the species. In the case of “Ayoteco”, incongruence between markers was observed. Low selection intensity, genetic flow events, and the plasticity of morphological traits may explain the high number of landraces without clear differences in their morphological diversity (vegetative characters) or genetic pools. The use of reproductive traits and massive sequencing might be useful for identifying possible morphological and genetic changes in the Agave landraces used for pulque production.